Non–Small-Cell Lung Cancer. Unusual Small Bowel Metastasis with Invagination - Miguel Ángel Serra Valdés; Briggette Fernández González; Mariana Medell Gago (Revista Finlay)
Malignant tumors, in Cuba, are the second leading cause of death after heart disease. Lung cancer is the leading cause of death worldwide in malignant tumors, predominantly in men. Non–small-cell lung cancer is the least common of all lung cancers. Metastases are recognized in the brain, ganglion, in the lungs, thyroid, liver, bones and adrenals. Metastasis in the small intestine is infrequent and there are few reports. It is presented the case of a 55-year-old female smoker with lung tumor and metastases in the lungs, lymph nodes, brain, thyroid and small intestine, which caused a mechanical occlusive acute abdomen due to invagination which accelerated the course and fatal outcome of this disease. The objective of this presentation is to let the scientific community know this case of a non-small cell carcinoma of the lung with intestinal metastasis giving an acute occlusive mechanical abdomen due to intestinal invagination.